Case report: Uterine perforation caused by migration of intrauterine devices - Li, Qi; Qi, Desheng; Bi, Tingting; Guo, Xinyi; Chen, Huan (Frontiers in Medicine, 2024)
Intrauterine devices (IUDs) are often considered a form of contraception by women of reproductive age because of their reversible, effective, safe, and convenient nature. However, its complications include bleeding, infection, displacement, and uterine perforation. As most patients do not exhibit any obvious symptoms, they ignore their complications and are unaware of the necessity of regular evaluation. Therefore, they are unable to implement timely interventions for the complications that can result in serious consequences. Although, three-dimensional (3D) ultrasound has demonstrated greater sensitivity in detecting subtle IUD malposition issues, particularly with side-arm embedment. Computed tomography (CT) scanning followed by multi-planar reformatting, maximum intensity projection, and volume rendering can precisely and intuitively display the morphology and location of the IUD, accurately exhibit the anatomical relationship between the IUD and the pelvis, and allow for a more accurate assessment of the degree of perforation and presence and absence of bowel perforation, thereby enabling us to select a more suitable surgical procedure with less damage to the patient. In this study, we reported an asymptomatic case of uterine perforation of the IUD into the serosal layer of the bladder, which developed 6 years post-IUD placement. A preoperative 3D reconstruction was made using the CT images of the IUD; then, the IUD was successfully removed with the assistance of a hysteroscope and laparoscope.